2020
DOI: 10.3390/f11111181
|View full text |Cite
|
Sign up to set email alerts
|

Pinus spp. Somatic Embryo Conversion under High Temperature: Effect on the Morphological and Physiological Characteristics of Plantlets

Abstract: Climatic variations in the current environmental scenario require plants with tolerance to sudden changes in temperature and a decrease in water availability. Accordingly, this tolerance will enable successful plantations and the maintenance of natural and planted forests. Consequently, in the last two decades, drought tolerance and high temperatures in conifers have been an important target for morphological, physiological, and epigenetic studies. Based on this, our research team has optimized different stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
1
16
2
Order By: Relevance
“…Priming using higher temperatures (up to 60 • C) improved somatic embryos production and altered amino acid [34] and CK profiles [35] of embryogenic masses (EMs), while regenerated plants showed differential patterns of gene expression and hormone content [36,37]. Similar experiments were carried out with Aleppo pine [38,39].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Priming using higher temperatures (up to 60 • C) improved somatic embryos production and altered amino acid [34] and CK profiles [35] of embryogenic masses (EMs), while regenerated plants showed differential patterns of gene expression and hormone content [36,37]. Similar experiments were carried out with Aleppo pine [38,39].…”
Section: Introductionmentioning
confidence: 77%
“…Thus, in maritime pine, increasing temperature from 23 to 28 • C during SE resulted in higher embryo yields [27]. In radiata pine, priming at high temperatures (>60 • C), applied at the induction or at maturation stages, produced variable germination responses and alterations in both morphology and stress responses [38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies carried out in our laboratory have demonstrated that P. radiata and P. halepensis showed different responses to abiotic stress such as drought and high temperature (do Nascimento et al, 2020). Also, in previous experiments, we have focused on the optimization of somatic embryogenesis (SE) processes.…”
Section: Introductionmentioning
confidence: 99%
“…Mazri et al [29] has suggested that for successful conversions to plantlets, it was essential for somatic embryos to first go through a maturation period which enables the embryos to reach physiological maturity. Further, in cases where 2,4-D was used to induce SE, the embryo maturation period should be conducted on supportive media containing activated charcoal to absorb any remaining 2,4-D. e auxin 2,4-D has been found to actively inhibit embryo conversion and plantlet recovery [29,30]. Contrary to the behavior of SE regenerates, plantlets regenerated via direct organogenesis grew vigorously strong, readily rooted, and could be subcultured several times.…”
Section: Discussionmentioning
confidence: 99%